A Circular Economy Approach: Total Elimination of Extreme Swelling in Expansive Clay Using Pyrolytic Carbon Black and Fly Ash - Hasrullah, Hasrullah; Mansur, Achmad Zultan (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: To rigorously investigate and quantify the effectiveness of a novel, synergistic stabilizer composed of Pyrolytic Carbon Black (PCB) and Fly Ash in totally eliminating extreme swelling potential in highly problematic expansive clay soil. Methodology: The comprehensive methodology included initial characterization, Modified Proctor compaction, One-Dimensional Swelling tests, Unconfined Compressive Strength (UCS) tests, and California Bearing Ratio (CBR) tests. Expansive clay was treated with a combined stabilizer dosage up to 25% (15% PCB and 10% Fly Ash) and cured for 28 days. Main Findings: The stabilizer significantly enhanced compaction characteristics, increasing the Maximum Dry Density (MDD) from 1.62 g/cm3 to 2.18 g/cm3. Crucially, the extreme Free Swell Index (FSI) of 120.23% was totally eliminated (swelling reduced to 0%). Mechanical strength improved dramatically: UCS increased from 0.12 kg/cm2 to 1.98 kg/cm2 , and unsoaked CBR enhanced from 2.48% to 10.18%. Novelty/Originality of this study: This research provides the first conclusive quantitative evidence of total swelling elimination in expansive clay using this specific PCB and Fly Ash sustainable blend. It advances knowledge by bridging geotechnical science, green engineering, and the circular economy, demonstrating a viable, cost-effective solution utilizing two major waste streams (tires and coal ash) for critical infrastructure subgrades.